Pengaruh Iklim Etika terhadap Kinerja Karyawan - Ngesti Agustina; Keumala Hayati (Penerbit Goodwood, 2023)
Purpose: This study aims to determine the effect of the ethical climate, which consists of collective moral sensitivity (moral awareness and empathic concern), collective moral judgment (self-focused and focus on others), and collective moral motivation on employee performance in private tertiary institutions in Bandar Lampung. Methodology/approach: This study uses primary data from the results of a questionnaire with a Likert scale. This quantitative research distributed questionnaires to 245 respondents from private universities in Bandar Lampung. The data analysis tool used was linear regression analysis with SPSS 25. Results/findings: The study's results show that collective moral sensitivity (moral awareness and empathic concern) does not affect performance, while collective moral judgment (focus on oneself and focus on others) and collective moral motivation affect performance. Conclusion: Based on the findings of this study, it is hoped that the leaders of private higher education can provide leadership and ethics training, build organizational member trust, build a culture of inclusiveness and proactivity, and improve a sense of belonging among organizational members.